STRATEGI PENANGANAN TEMPER TANTRUM PADA ANAK DI PENDIDIKAN ANAK USIA DINI - Ade Rahmita; Faizatul Faridy; Shabrina Saleem; Najwa Muthmainnah (STKIP Subang, 2026)
Temper tantrums in early childhood education remain a significant challenge due to children’s limited emotional regulation and the lack of evidence-based handling strategies implemented by educators and parents. This study aims to analyze strategies for managing temper tantrums in early childhood education settings through a literature review approach. The research employed a qualitative library research method by examining fifteen relevant scientific articles published between 2016 and 2026 from reputable national and international journals. Data were collected through systematic literature selection and analyzed using content analysis techniques involving data reduction, categorization, interpretation, and synthesis. The findings indicate that effective strategies for handling temper tantrums include strengthening positive teacher-child interactions, implementing structured classroom management, applying positive reinforcement, integrating play-based learning activities, involving parents actively in behavior management, and creating emotionally supportive learning environments. Preventive interventions that focus on developing children’s emotional regulation skills from an early age were also found to significantly reduce the frequency and intensity of tantrum behaviors. The study concludes that effective temper tantrum management requires a holistic and collaborative approach involving teachers, parents, and educational institutions to support optimal social-emotional development in early childhood. These findings provide practical implications for educators in designing responsive and evidence-based intervention strategies in early childhood education settings.